2022
DOI: 10.3390/horticulturae8080673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrient Solution Electrical Conductivity on the Leaf Gas Exchange, Biochemical Stress Markers, Growth, Stigma Yield, and Daughter Corm Yield of Saffron in a Plant Factory

Abstract: Indoor saffron farming systems under controlled conditions are required to meet the high demand for this valuable crop. The aim of the present study was to determine the flowering, growth, and yield responses of saffron grown using nutrient solutions with different electrical conductivity (EC) levels (0.7, 1.4, and 2.1 dS m−1). Sprouted saffron corms were cultured for 24 weeks under a volcanic rock-based aerated continuous immersion system. Vegetative growth and leaf gas exchange, but not flowering, were affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…In the present experiment, it was shown that the complete replacement of the nutrient solution and the EC-based replacement method led to an increase in antioxidant enzymes in both lettuce varieties. This is consistent with previous founding in basil and saffron plants, where increasing the concentration of the Hoagland nutrient solution provoked an increase in both enzymatic and non-enzymatic antioxidants 57 , 58 . The high activity of antioxidant enzymes observed in treatments with high EC levels could be explained by the direct toxic effect of the minerals accumulating at high levels and by a negative effect on water uptake, provoking dehydration symptoms 59 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present experiment, it was shown that the complete replacement of the nutrient solution and the EC-based replacement method led to an increase in antioxidant enzymes in both lettuce varieties. This is consistent with previous founding in basil and saffron plants, where increasing the concentration of the Hoagland nutrient solution provoked an increase in both enzymatic and non-enzymatic antioxidants 57 , 58 . The high activity of antioxidant enzymes observed in treatments with high EC levels could be explained by the direct toxic effect of the minerals accumulating at high levels and by a negative effect on water uptake, provoking dehydration symptoms 59 .…”
Section: Discussionsupporting
confidence: 93%
“…The environmental conditions of the growth chamber were adjusted to 15 • C ± 1 • C and 70 µmol m −2 s −1 photosynthetic photon flux density (PPFD) for a 16 h photoperiod using cool white fluorescent lamps. The flowering characteristics, i.e., the number of flowers per plant, stigma length, and stigma fresh and dry weights, under in vitro culture were compared with those under an aerated, volcanic-rock-based hydroponic system as described by Dewir and Alsadon [16]. The corms were obtained from the same source (Bloembollenbedrijf J.C.Koot) and were of the same size grade (3.2-3.5 cm diameters).…”
Section: Saffron Flowering In In Vitro Culture and Hydroponic Culturementioning
confidence: 99%
“…Comparison of stigma and flower size of saffron produced under in vitro culture and via a hydroponic system (Dewir and Alsadon[16]). …”
mentioning
confidence: 99%